Knowledge-Based Economies and Basing Economies on Knowledge Skills a Missing Link in GCC Countries - Kumar, Krishna B. (RAND Corporation, 2013)
In addition to an Information and Communication Technology infrastructure, a skilled labor force and a supportive environment are necessary to the balanced development of a knowledge-based economy. Without sufficient human capital and policies in place to promote the use of adopted technologies, their full potential may not be realized. This paper uses a cross-country perspective and various economic indicators to assess the development of Gulf Cooperation Council countries in the dimensions of a knowledge economy.